(untitled) - Durston, Diane (New York,Tokyo, 1986)
Old Kyoto guides you with a practiced hand and 51 maps and over 120 photos to the living heart of this ancient capital, to the favored haunts and shops. For the archiar traveler, and of a vanishing way of life. it has captured with an unerring eye, the elusive charms and hideaways of one of the world's most enchanting cities.